Google/Yandex Translation Detection in the Patterns Identifying System of Multilingual Texts - Kulikov, Vladimir; Kulikova, Valentina; Yerkebulan, Gulnur (International Journal of Computing, 2021)
The object of this work is to develop a script for evaluating the ability of online translators to translate text from one language to another. For this purpose, we used Google Translate and Yandex.Translate. Examples from English, Kazakh and Russian languages were used for the analysis of 147 news items and about 1800 sentences. The texts are taken from an Internet resource astana.gov.kz. A corpus of parallel texts for three languages has been created. We used development for the “sentence” pattern with the prospect of further development for the “text” pattern. We analyzed errors in the following categories: untranslated/omitted words, extra words, incorrect word endings, incorrect word order, punctuation errors, mutilate translation and incorrect translation. Based on the analysis of the obtained data we have concluded that it is better to do the translation of the Russian text into Kazakh or English in the YandexTranslate than in Google Translate. The developed comparison script and error analysis script are available on the Internet in open access.